If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + 3) = 36 Reorder the terms: 4(3 + 5x) = 36 (3 * 4 + 5x * 4) = 36 (12 + 20x) = 36 Solving 12 + 20x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 20x = 36 + -12 Combine like terms: 12 + -12 = 0 0 + 20x = 36 + -12 20x = 36 + -12 Combine like terms: 36 + -12 = 24 20x = 24 Divide each side by '20'. x = 1.2 Simplifying x = 1.2
| 3(x+3)-2=-5 | | 9n^2=-192+96n | | 3z-2=2(2z-5) | | 3(2x+1)-4=6x-1 | | 6b-9b=10(1-b)+9b+18 | | x^2+10x+137=0 | | 4x+3=2(2x+1.5) | | f(x)=-16x^2+50x | | 4x+3=3-(3x-3) | | 9x^2+32x-16=0 | | 6x+4y-2x+y= | | 2x+3=4-(8x-3) | | 12x^2=30x+150 | | -3(k+5)=3(k+1) | | 4x^3+sinx= | | 5(x-1)-2x=7 | | log(2x-7)=2 | | 49x^2+14x-840=0 | | 2(x+2)-3=7 | | 4-(y-3)=3(y+1)-4(1-y) | | 6x=x^2-40 | | 49x^2-14x+840=0 | | .85=-log(x) | | 6a+6= | | 3000=-16t^2+480t+10 | | y=-7-(2k+3)x | | 24k^2+184k=-240 | | .2x-.7x-6=5 | | 1225=10a+30b | | log(4x+9)=1+log(x-2) | | 4=5(x+8)-5(x-5) | | a=117.8+-2b |